2017
DOI: 10.1177/2041669517738542
|View full text |Cite
|
Sign up to set email alerts
|

50 Years of Stereoblindness: Reconciliation of a Continuum of Disparity Detectors With Blindness for Disparity in Near or Far Depth

Abstract: Whitman Richards (1932–2016) discovered some 50 years ago that about 30% of observers from the normal population exhibit stereoblindness: the disability to process binocular disparities in either far or near depth. We review the literature on stereoblindness entailing two insights. First, contemporary scholars in stereopsis undervalue the comprehension that disparity processing studies require precise assessments of observers’ stereoblindness. We argue that this frequently leads to suboptimal interpretations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Moreover, our sample was only screened for stereoability by using the TNO, which is based on red-green anaglyphs. Thus, the effect sizes in the current data might be diminished by inter-individual differences in stereoability (Dorman & van Ee, 2017;Kooi et al, 2010;van Ee & Richards, 2002) and could have benefited from a stricter criterion (Westheimer, 2013). For example, van Ee and Richards (2002) propose a more elaborate test of stereovision.…”
Section: Effects Of Defocus Blur and Disparitymentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, our sample was only screened for stereoability by using the TNO, which is based on red-green anaglyphs. Thus, the effect sizes in the current data might be diminished by inter-individual differences in stereoability (Dorman & van Ee, 2017;Kooi et al, 2010;van Ee & Richards, 2002) and could have benefited from a stricter criterion (Westheimer, 2013). For example, van Ee and Richards (2002) propose a more elaborate test of stereovision.…”
Section: Effects Of Defocus Blur and Disparitymentioning
confidence: 82%
“…A blank screen afterward ensured that stimuli remained in the iconic memory for processing (Sperling, 1960). In addition, within a presentation duration of 20 ms accommodative (e.g., Kasthurirangan & Glasser, 2006) or vergence movements (e.g., Bucci, Kapoula, Yang, & Bremond-Gignac, 2006) were impossible (see also Dorman & van Ee, 2017). Participants were instructed to release the starting key and indicate the opening direction of the target Landolt ring as fast and as correctly as possible.…”
Section: Methodsmentioning
confidence: 99%
“…According to the first view, each is processed in separate systems (see Mustillo). According to the opposite view, there is a continuum of disparity sensitivities . Whether one view or the other is correct, the important fact is the following: some observers can show normal stereoacuity for one type of disparity and be stereoblind to the other .…”
Section: How To Measure Stereoacuity For Determining Stereoblindness?mentioning
confidence: 99%
“…Human stereoacuity thresholds smaller than 5 seconds of arc (arcsec) have been obtained (McKee, 1983;Stevenson, Cormack, & Schor, 1989). Previous studies, however, have shown considerable individual differences in stereoacuity across the population (Bosten et al, 2015;Dorman & van Ee, 2017;Hess et al, 2015;Hess et al, 2016;Zaroff, Knutelska, & Frumkes, 2003). In this study, we investigate the variability for a relative disparity detection task.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, these results can also be explained by a model in which stereo processing occurs in a series of stages. If the direction of the disparity is determined at a relatively late stage, then it may be this step that is failing (Dorman & van Ee, 2017;Landers & Cormack, 1997).…”
Section: Introductionmentioning
confidence: 99%